Shaping Turkey's futurediscourse : political Islam or civil Islam - Mohammed Nawab Mohamed Osman (2014)
The current political impasse in Turkey has brought to light the contest between political Islam represented by the ruling Justice and Development Party (AKP) and civil Islam embodied by the Hizmet movement inspired by Turkish imam and philosopher Fethullah Gulen. The outcome will have significant impact on Turkey and the larger Muslim world.